Time‐driven activity‐based costing to estimate cost of care at multidisciplinary aerodigestive centers. (21st June 2017) - Garcia, Jordan A.; Mistry, Bipin; Hardy, Stephen; Fracchia, Mary Shannon; Hersh, Cheryl; Wentland, Carissa; Vadakekalam, Joseph; Kaplan, Robert; Hartnick, Christopher J.
Abstract : Objectives/Hypothesis: Providing high‐value healthcare to patients is increasingly becoming an objective for providers including those at multidisciplinary aerodigestive centers. Measuring value has two components: 1) identify relevant health outcomes and 2) determine relevant treatment costs. Via their inherent structure, multidisciplinary care units consolidate care for complex patients. However, their potential impact on decreasing healthcare costs is less clear. The goal of this study was to estimate the potential cost savings of treating patients with laryngeal clefts at multidisciplinary aerodigestive centers. Study Design: Retrospective chart review. Methods: Time‐driven activity‐based costing was used to estimate the cost of care for patients with laryngeal cleft seen between 2008 and 2013 at the Massachusetts Eye and Ear Infirmary Pediatric Aerodigestive Center. Retrospective chart review was performed to identify clinic utilization by patients as well as patient diet outcomes after treatment. Patients were stratified into neurologically complex and neurologically noncomplex groups. Results: The cost of care for patients requiring surgical intervention was five and three times as expensive of the cost of care for patients not requiring surgery for neurologically noncomplex and complex patients, respectively. Following treatment, 50% and 55% of complex and noncomplex patients returned to normal diet, whereas 83% and 87% of patients experienced improved diets, respectively. Additionally, multidisciplinary team‐based care for children with laryngeal clefts potentially achieves 20% to 40% cost savings. Conclusions: These findings demonstrate how time‐driven activity‐based costing can be used to estimate and compare patient costs in multidisciplinary aerodigestive centers. Level of Evidence: 2c. Laryngoscope, 127:2152–2158, 2017